A prospective study of intravenous pentamidine for PJP prophylaxis in adult patients undergoing intensive chemotherapy or hematopoietic stem cell transplant. (March 2018) - Sweiss, Karen; Anderson, Jennifer; Wirth, Scott; Oh, Annie; Quigley, John; Khan, Irum; Saraf, Santosh; Mactal-Haaf, Christina; Rondelli, Damiano; Patel, Pritesh
Abstract Prophylaxis forPneumocystis jirovecii pneumonia (PJP) is recommended for patients undergoing hematopoietic stem cell transplantation (HSCT) or intensive chemotherapy. Trimethoprim–sulfamethoxazole and inhaled pentamidine are used frequently, but are limited, by their tolerability and therefore compliance. Intravenous (IV) pentamidine is a potential alternative agent. Here we conducted the first prospective study of the safety and efficacy of IV pentamidine for PJP prophylaxis in adult patients undergoing HSCT or intensive chemotherapy (clinicaltrials.gov NCT02669706). Fifty patients requiring PJP prophylaxis were enrolled and received monthly IV pentamidine at 4 mg/kg (maximum 300 mg) while undergoing intensive chemotherapy or HSCT. Patients were followed for the occurrence of PJP pneumonia and for adverse events. Satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication (TSQM Version 1.4) survey. Seventeen (34%) patients experienced a grade 1 or 2 adverse event. There were no grade 3/4 events. The TSQM questionnaire indicated that the majority of patients were satisfied with the administration of IV pentamidine (n = 43, 86%, p = 0.01). There were no cases of PJP during the 24 month follow-up period. Our study illustrates the safety, feasibility, and high degree of patient satisfaction when using IV pentamidine for PJP prophylaxis.